Experimental Treatment of Ebola Virus Disease with Brincidofovir. - Jake Dunning; Stephen B Kennedy; Annick Antierens; John Whitehead; Iza Ciglenecki; Gail Carson; Rupa Kanapathipillai; Lyndsey Castle; Rebecca Howell-Jones; Raul Pardinaz-Solis; Jennifer Grove; Janet Scott; et al. (PLoS ONE)
Background The nucleotide analogue brincidofovir was developed to prevent and treat infections caused by double-stranded DNA viruses. Based on in vitro data suggesting an antiviral effect against Ebola virus, brincidofovir was included in the World Health Organisation list of agents that should be prioritised for clinical evaluation in patients with Ebola virus disease (EVD) during the West African epidemic. Methods and findings In this single-arm phase 2 trial conducted in Liberia, patients with laboratory-confirmed EVD (two months of age or older, enrolment bodyweight ≥50 kg) received oral brincidofovir 200 mg as a loading dose on day 0, followed by 100 mg brincidofovir on days 3, 7, 10, and 14. Bodyweight-adjusted dosing was used for patients weighing <50 kg at enrolment. The primary outcome was survival at Day 14 after the first dose of brincidofovir. Four patients were enrolled between 01 January 2015 and 31 January 2015. The trial was stopped following the decision by the manufacturer to terminate their program of development of brincidofovir for EVD. No Serious Adverse Reactions or Suspected Unexpected Serious Adverse Reactions were identified. All enrolled subjects died of an illness consistent with EVD. Conclusions Due to the small sample size it was not possible to determine the efficacy of brincidofovir for the treatment of EVD. The premature termination of the trial highlights the need to establish better practices for preclinical in-vitro and animal screening of therapeutics for potentially emerging epidemic infectious diseases prior to their use in patients. Trial registration Pan African Clinical Trials Registry PACTR201411000939962.